Pengujian Cup Drawing Pada Plat TipisDengan Sambungan Las Titik, Tekuk,Dan Tanpa Sambungan - Santoso, Budi; , Agus Dwi Anggono, ST., M.Eng., Ph.D (2016)
Blank is a very important part in the trials for drawing and a vital part in preventing the wrinkling defect . At the time of the drawing process is underway , the role of blank indispensable so that defects can be a little wrinkling resolved. Related to that then by doing variations on blank disks can be revealed the influence of variation on the outcome of the process of drawing cup. In conducting this research aims to identify the occurrence of wrinkling defects in the process of drawing cup with three variations of blank or plate, and knowing wrinkling defects in the process of drawing cup. Furthermore, by making a blank with a material that has been determined. There are three variations of cup drawing blanks in this research is the connection spot welding, bending, and without connection. This study uses research methods cup drawing with cylindrical plate. The resulting product is a cup with a top diameter d1: 46 mm, bottom diameter d2: 30 mm and a depth h: 15 mm. Blank material used is platalumunium with plate thickness of 0.2 mm. The results showed that the best results are in the wear plate blank without using a connection that has a defect depth to its lowest wrinkling of 0.38 mm, for disks that use the connection plate spot welding defects produce wrinkling highest depth of 1.5 mm, and in experiment with a blank plate buckling disability loose connection on the connection